Analysis of competition warm-up and re-warm-up practices of Portuguese basketball coaches - Luís M. Silva; Henrique Pereira Neiva; Daniel Almeida Marinho (Motricidade)
Basketball is a dynamic team sport characterised by intense, strategic play that requires high-intensity activities such as sprinting, jumping, and changing direction. Proper warm-up (WU) routines are crucial for improving athletic performance and adapting to the game’s physical demands. This study evaluates the WU practices of Portuguese basketball coaches and their adherence to evidence-based guidelines. A cross-sectional survey of 158 Portuguese basketball coaches was conducted to analyse the relationships between their WU and re-warm-up (RWU) strategies and the coached competition. Significant associations in WU were found among coaches of youth competitions and performance competitions, especially in WU volume, but no significant associations were found regarding in-game or halftime RWU strategies. This study shows that coaches in performance contexts tend to use more comprehensive WU strategies. However, there is a need for increased practice of RWU routines by the coaches of youth and performance competitions to optimise player performance.